Sex Differences in the Neuropeptide Y System and Implications for Stress Related Disorders - Roxanna J. Nahvi; Esther L. Sabban (Biomolecules, 2020)
The neuropeptide Y (NPY) system is emerging as a promising therapeutic target for neuropsychiatric disorders by intranasal delivery to the brain. However, the vast majority of underlying research has been performed with males despite females being twice as susceptible to many stress-triggered disorders such as posttraumatic stress disorder, depression, anorexia nervosa, and anxiety disorders. Here, we review sex differences in the NPY system in basal and stressed conditions and how it relates to varied susceptibility to stress-related disorders. The majority of studies demonstrate that NPY expression in many brain areas under basal, unstressed conditions is lower in females than in males. This could put them at a disadvantage in dealing with stress. Knock out animals and Flinders genetic models show that NPY is important for attenuating depression in both sexes, while its effects on anxiety appear more pronounced in males. In females, NPY expression after exposure to stress may depend on age, timing, and nature and duration of the stressors and may be especially pronounced in the catecholaminergic systems. Furthermore, alterations in NPY receptor expression and affinity may contribute to the sex differences in the NPY system. Overall, the review highlights the important role of NPY and sex differences in manifestation of neuropsychiatric disorders.